2014
DOI: 10.1016/j.cub.2013.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of Brain Oscillations by Transcranial Alternating Current Stimulation

Abstract: Novel methods for neuronal entrainment [1-4] provide the unique opportunity to modulate perceptually relevant brain oscillations [5, 6] in a frequency-specific manner and to study their functional impact on distinct cognitive functions. Recently, evidence has emerged that tACS (transcranial alternating current stimulation) can modulate cortical oscillations [7-9]. However, the study of electrophysiological effects has been hampered so far by the absence of concurrent electroencephalogram (EEG) recordings. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
799
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(840 citation statements)
references
References 41 publications
(60 reference statements)
31
799
7
3
Order By: Relevance
“…Ai & Ro, 2014;Lakatos, Karmos, Mehta, Ulbert, & Schroeder, 2008;Sherman et al, 2016) and may have other relationships with performance than the overall state as indexed here. Future investigations which directly manipulate ongoing oscillations through methods such as transcranial alternating current stimulation (Helfrich et al, 2014;Herrmann, Murray, Ionta, Hutt, & Lefebvre, 2016;Vosskuhl, Huster, & Herrmann, 2016) would help to answer these questions more directly.…”
Section: Discussionmentioning
confidence: 99%
“…Ai & Ro, 2014;Lakatos, Karmos, Mehta, Ulbert, & Schroeder, 2008;Sherman et al, 2016) and may have other relationships with performance than the overall state as indexed here. Future investigations which directly manipulate ongoing oscillations through methods such as transcranial alternating current stimulation (Helfrich et al, 2014;Herrmann, Murray, Ionta, Hutt, & Lefebvre, 2016;Vosskuhl, Huster, & Herrmann, 2016) would help to answer these questions more directly.…”
Section: Discussionmentioning
confidence: 99%
“…Different from tDCS, tACS has no major plasticity-inducing effect [22] , although recent studies suggest that exceptions do exist [23] . Modelling and animal and human studies have shown that relatively focal AC stimulation can lead to widespread entrainment of oscillatory activity at the induced frequency [24,25] . The main effect of tACS in humans is a modulation of oscillatory frequency bands in the EEG, if these match the stimulation frequency.…”
Section: Physiology Of Transcranial Electrical Stimulationmentioning
confidence: 99%
“…Finally, an oscillatory variant of tDCS, referred to as transcranial alternating current stimulation (tACS) applies a regular oscillating current (c.f., tRNS) across the two electrodes. This stimulation approach is thought to be efficient in changing neural oscillations in the targeted region (Marshall and Binder, 2013;Helfrich et al, 2014) and is discussed in more detail later in the review.…”
Section: Transcranial Electrical Stimulationmentioning
confidence: 99%
“…The task-related boosting (or suppression) of neural oscillations at specific frequencies between cortical regions can enhance performance in processes involved in task selection, attention and memory (Marshall et al, 2004;Lakatos et al, 2008;Bauer et al, 2012;Helfrich et al, 2014). Both rTMS and tDCS can modify ongoing oscillatory activity, and in so doing, may mimic or augment the amplitude of normal endogenous neural oscillations to promote task performance and cortical connectivity.…”
Section: Modulating Local Cortical Synchronizationmentioning
confidence: 99%
See 1 more Smart Citation